The Relationship of Irisin with Leptin and Testosterone Hormones in Students of the College of Physical Education and Sports Sciences / Tikrit University - Hana Attiya Salman; Iktefaa Abdul- Hameed (Tikrit Journal of Pure Science, 2022)
Sports it is the best way to activate the vital processes of different organs of the body hormones affect the vital activity of living organisms, so physiological changes occur across all body systems as a result of exercise. The study aims to find out the effect of anaerobic exercise on the concentrations of  irisin hormone and some of the hormonal variables in male sports practitioners, and the correlation between the hormone and the studied variables, the correlation between hormones with each other, and the correlation between the body mass criterion and the studied variables to find out the extent of the body mass criterion related to the variables and the extent of the correlation of the hormone irisin with the variables and the extent of the linkage of hormones with each other during anaerobic exercise. The study included (20) samples of blood from senior male volleyball players of the college of physical education and sports sciences in Tikrit University. Their age ranged from 21 to 26 years old and the duration of November 2018 to January 2019. As 40 blood samples were collected, blood samples were collected on the same day and for once fifteen minutes before the start of the exercise, and again ten minutes after the end of the exercise that lasted for an hour and a half. The results of the study indicated the absence of moral differences in the level of concentration of both irisin, and testosterone hormones in the group of volleyball players after the performance of the exercise compared to before exercise and Also the study showed a decrease in the moral level of the concentration of leptin hormone in the group of volleyball players after the performance of the exercise compared to before the exercise.